Pengembangan Media Video Pada Materi Degung Untuk Meningkatkan Pegetahuan Siswa Pada Pelajaran Seni Budaya Kelas V Di SDN Candraniti - Zidan Haidar, Mohammad; Nugraha, M. Fahmi; Permana, Rahmat (Journal of Elementary Education: Strategies, Innovations, Curriculum, and Assesment, 2024)
This research aims to develop and determine the effectiveness of Degung Video Media in improving learning outcomes in class V Traditional Music material in elementary schools. The method used in this research is Research and Development type with 10 stages. However, this research is focused on stage 7. The research location is SDN Candraniti with subjects in grade 5 of elementary school. Data collection in this research was observation, interviews, questionnaires and tests. Meanwhile, the data analysis techniques used are qualitative analysis and quantitative analysis as well as analysis of student test results in the form of pretest and posttest. The results of this research are: (1) Degung Video media is suitable for use with the final media expert validation result being 3.75 in the "Very Good" category. Material expert validation was 4.00 and 3.57 in the "Very Good" category. Linguist validation is 4.00 in the "Very Good" category. (2) The assessment in the small group trial received an average score of 3.90 or in the "Very Good" category and in the large group trial it received an average score of 3.80 in the "Very Good" category. These results show that the Degung Video media is very suitable for use as a media for learning arts and culture in traditional material for class V elementary school. (3) The results of the pretest and posttest showed significant changes. The average initial or pretest score is 45 while the average posttest is 81. These results show that the average posttest result is greater than the average pretest result. The effectiveness of the media as measured using N-Gain received an average score of 0.7, including in the "high" category, so it can be concluded that using learning media is more effective and greatly improves arts and culture learning outcomes in Traditional Music Arts material at SDN Candraniti.